Histophysiology of the spleen after application of medroxyprogesterone acetate - ES Mitevska; ZA Gerasimovska; LS Kakaseva; DK Trajkov; MR Jurhar; PE Stojoska; MZ Spiroski (My University, 1998)
The aim of our study was to determine the activity of medroxiprogesterone acetate (MPA) on the histophysiology of the biggest lymphatical organ, the spleen. The experiment was performed using 24 female Wister rats. The first, control group of 12 rats received physiological solution daily, whereas the other group, MPA in a dose of 15.0 mg/kg bw intramuscularly in a period of 30 days. The histological analysis of the spleen showed an obvious reduction of the lymph follicles which were in an involuntary phase with inactive germinal centers. Destructive changes in tissue were registered in the close distance of which a more intensive development of connective tissue was noticed into which collagen fibres predominate. The stereological analysis showed decrease of volume density of the white pulp from 13,42 ± 2,12% (medium value ± standard deviation) to 7,14 ± 1,92% (p < 0,001). The volume density of the marginal zone increased from 36,91 ± 4,44% to 52,38 ±15,14% (p< 0,001) and the volume density of the red pulp dropped from 49,69 ± 5,18% to 38,1 ± 7,15% (p< 0,001).
Хистофизиологија слезине након апликације медроксипрогестерон ацетата